Does Compliance to Green Bond Principles Matter? Global Evidence - Madurika Nanayakkara; Sisira Colombage (Australasian Accounting, Business and Finance Journal, 2022)
We examine the effect of degree of compliance with the Green Bond Principles (GBP) on investor demand for such bonds, using cross-sectional data for all countries in the Green Bond market over the period 2007-2019. We find a significantly positive effect of higher compliance with the GBPs on investor demand, as measured by Bid-Ask-Spread and Yield-spread, after controlling for common bond-specific and macroeconomic variables. However, our results showed no evidence that macroeconomic factors influenced Green Bond investments. Moreover, we also find a positive effect on investor demand when a bond is issued by a government agency, even if the degree of compliance is low.
Keywords: Bond Market; Bid-ask spread; Green Bonds; Green Bond Principles; Compliance; Investor demand; Sustainability